Differences in Developmental Concerns of Young Children with Autism Spectrum Disorder Across Racial/Ethnic Groups. (3rd April 2019) - Issarraras, Abigail; Matson, Johnny L.; Matheis, Maya; Burns, Claire O.
ABSTRACT: Purpose : Parents/caregivers of children with autism spectrum disorder (ASD) have varying types of initial concerns regarding their child's development, which may be culturally bound to parents' perceptions of their child's development. This study investigated differences in the types of initial developmental concerns reported by parents or caregivers of different racial/ethnic groups with children in an early intervention program. Method : This study examined the frequency of endorsement of different types of concerns in African American, Caucasian, and Hispanic families. Results : No significant differences between racial/ethnic groups were found in the endorsement of concerns related to communication, language/speech, motor, problem behavior, sensory, feeding, prematurity, attention, adaptive functioning, and medical conditions. Racial/ethnic groups differed significantly in their endorsement for social concerns. Conclusion : Racial/ethnic group differences were confirmed regarding initial developmental concerns related to social behavior, which may be due to cultural beliefs. The implications of these findings on early identification are discussed.